INNOVATION OF BRANDED SUGAR ANTS IN INCREASING SALES IN BLANG BATEE VILLAGE, PEUREULAK DISTRICT - Siti Sahara; Meta Suriyani; Safuridar Safuridar; Liza Agnesta Krisna (Global Science Society, 2022)
Palm sugar, one of the staple foods. Processing is very easy, as a food sweetener and good for health because it is without preservatives. So far, palm sugar farmers in Blang Batee Village, Peureulak District, only know and make palm sugar by printing it in solid form or hardening it. They don't understand if there is an innovation that is made into a form of granulated sugar or ant sugar. Molded palm sugar packaging, wrapped in dried banana leaves and tied with rope. Marketing only sells in the local market on a limited basis. The solution is to help the community in innovating solid palm sugar into palm sugar and candied liquid palm sugar to improve product quality, packaged in a modern way, branded and marketed offline and online. This is done to increase sales and profits.